Keabsahan Pengangkatan Anak Piara Mantan Raja Sebagai Kepala Pemerintah Negeri (Desa) - Firmansyah, Mohamad Z; Bakarbessy, Andress Denny; Pattinasarany, Yohanes (Faculty of Law Universitas Pattimura, 2025)
Article 3 paragraph (2) of the Malteng Regional Regulation No. 1 of 2006 stipulates that